2016
DOI: 10.1186/s12891-016-0999-6
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells and bFGF in tendon healing: Effects of lentiviral gene transfer and long-term follow-up in a rat Achilles tendon defect model

Abstract: BackgroundThe influence of stem cells and lentiviral expression of basic fibroblastic growth factor (bFGF) on tendon healing and remodelling was investigated in an in-vivo long-term (12 weeks) rat Achilles tendon defect model.MethodsIn sixty male Lewis rats, complete tendon defects (2.4 mm) were created and either left untreated (PBS) or treated by injection of stem cells lentivirally expressing the enhanced green fluorescence marker gene eGFP (MSC-LV-eGFP) or basic fibroblast growth factor bFGF (MSC-LV-bFGF).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Much evidence supports the use of GFs to enhance tendon healing (Docheva et al, 2015;Evans, 1999;Molloy et al, 2003;Sharma and Maffulli, 2006), but numerous issues remain to be resolved, including which GFs to use and when and how to deliver them. Single GFs provide little benefit or only incremental improvement to tendon healing in vitro and in animal models (Chan et al, 2000;Feng et al, 2007;Forslund and Aspenberg, 2001;Gelberman et al, 2016;Kashiwagi et al, 2004;Klein et al, 2002;Kraus et al, 2016;Kraus et al, 2014;Majewski et al, 2008;Majewski et al, 2012;Tang et al, 2008;Wang et al, 2005b), suggesting that mixtures of different GFs may be necessary to modulate the complex process of tendon healing in a substantial manner. This may explain why ACS and PRP show some ability to improve tendon healing (Aspenberg and Virchenko, 2004;Bosch et al, 2010;de Almeida et al, 2012;Gosens et al, 2012;Majewski et al, 2009;Parafioriti et al, 2011;Schnabel et al, 2007;Seijas et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much evidence supports the use of GFs to enhance tendon healing (Docheva et al, 2015;Evans, 1999;Molloy et al, 2003;Sharma and Maffulli, 2006), but numerous issues remain to be resolved, including which GFs to use and when and how to deliver them. Single GFs provide little benefit or only incremental improvement to tendon healing in vitro and in animal models (Chan et al, 2000;Feng et al, 2007;Forslund and Aspenberg, 2001;Gelberman et al, 2016;Kashiwagi et al, 2004;Klein et al, 2002;Kraus et al, 2016;Kraus et al, 2014;Majewski et al, 2008;Majewski et al, 2012;Tang et al, 2008;Wang et al, 2005b), suggesting that mixtures of different GFs may be necessary to modulate the complex process of tendon healing in a substantial manner. This may explain why ACS and PRP show some ability to improve tendon healing (Aspenberg and Virchenko, 2004;Bosch et al, 2010;de Almeida et al, 2012;Gosens et al, 2012;Majewski et al, 2009;Parafioriti et al, 2011;Schnabel et al, 2007;Seijas et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bFGF gene transfer increases expression of type I and type III collagen in vitro (Feng et al, 2007;Wang et al, 2005b). However, promising results demonstrating improved tendon healing by bFGF gene transfer (Tang et al, 2008) are not reproducible (Kraus et al, 2016;Kraus et al, 2014). In a small series of 8 rabbits, Achilles tendons heal better than controls if treated with bFGF (Najafbeygi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the focus was particularly on the injury of the tendon tissue. Philippou A et al reported that the local production of IGF-1 is particularly important in regeneration, hypertrophy, proliferation, and differentiation of skeletal muscles 17) . In another study by Duman et al, the effects of rectal ozone therapy on femur fracture in rats were evaluated 18) .…”
Section: Discussionmentioning
confidence: 99%
“…bFGF belongs to the heparin-binding growth factor family. Previous studies [ 37 , 38 ] have reported that bFGF and TGF can be used to improve the bioactivity of osteoblasts and promote the aggregation of fibroblast and inflammatory cells, further enhancing the formation of blood vessels and granulation tissue.…”
Section: Discussionmentioning
confidence: 99%